Investigating nicotine pathway-related long non-coding RNAs in tobacco - Xie, Xiaodong; Jin, Jingjing; Wang, Chen; Lu, Peng; Li, Zefeng; Tao, Jiemeng; Cao, Peijian; Xu, Yalong (Frontiers in Genetics, 2023)
Long noncoding RNAs (lncRNAs) are transcripts longer than 200bp with low or no protein-coding ability, which play essential roles in various biological processes in plants. Tobacco is an ideal model plant for studying nicotine biosynthesis and metabolism, and there is little research on lncRNAs in this field. Therefore, how to take advantage of the mature tobacco system to profoundly investigate the lncRNAs involved in the nicotine pathway is intriguing. By exploiting 549 public RNA-Seq datasets of tobacco, 30,212 lncRNA candidates were identified, including 24,084 large intervening noncoding RNAs (lincRNAs), 5,778 natural antisense transcripts (NATs) and 350 intronic noncoding RNAs (incRNAs). Compared with protein-coding genes, lncRNAs have distinct properties in terms of exon number, sequence length, A/U content, and tissue-specific expression pattern. lincRNAs showed an asymmetric evolutionary pattern, with a higher proportion (68.71%) expressed from the Nicotiana sylvestris (S) subgenome. We predicted the potential cis/trans-regulatory effects on protein-coding genes. One hundred four lncRNAs were detected as precursors of 30 known microRNA (miRNA) family members, and 110 lncRNAs were expected to be the potential endogenous target mimics for 39 miRNAs. By combining the results of weighted gene co-expression network analysis with the differentially expressed gene analysis of topping RNA-seq data, we constructed a sub-network containing eight lncRNAs and 25 nicotine-related coding genes. We confirmed that the expression of seven lncRNAs could be affected by MeJA treatment and may be controlled by the transcription factor NtMYC2 using a quantitative PCR assay and gene editing. The results suggested that lncRNAs are involved in the nicotine pathway. Our findings further deepened the understanding of the features and functions of lncRNAs and provided new candidates for regulating nicotine biosynthesis in tobacco.